Fecal thyroid hormone metabolites in wild ungulates: a mini-review - Pasciu, Valeria; Nieddu, Maria; Sotgiu, Francesca Daniela; Baralla, Elena; Berlinguer, Fiammetta (Frontiers in Veterinary Science, 2024)
This review aims to analyse the fluctuations of fecal thyroid hormone metabolites (FTMs) related to environmental and individual variables in different species of wild ungulates and provide a collection of assay methods. The great advantage of fecal sampling is being completely non-invasive. A systemic search was conducted from 2019 to 2024, using data sources PubMed, Scopus, Web of Science, and the World Wide Web, and ten studies were found on this topic. Three studies used the radioimmunoassay method for FTMs analysis, while the others used a less expensive enzyme-linked immunosorbent assay. Most of these papers validated the method for the species-specific matrix. Related to the studied variables, some authors analysed FTM fluctuations only concerning individual variables, and others in response to both. Temperature and fecal cortisol metabolites (FCMs) were the most studied environmental and individual variables, respectively. Since FTMs are an integrative measure of plasma thyroid hormones, the information obtained from a noninvasive-assay method regarding wild ungulate physiology is becoming of great interest to the scientific community.